The association between hepatitis C virus infection status and blood pressure in adults in the United States: NHANES 1999–2012 - Yang, Feng; Luo, Jianping (Frontiers in Cellular and Infection Microbiology, 2024)
Background The Hepatitis C virus (HCV) infection is strongly associated with cardiovascular disease risk factors, but the relationship with blood pressure (BP) remains unclear. Objectives To assess the association between HCV infection status and BP in US adults. Methods Data for the study were obtained from the National Health and Nutrition Examination Survey (NHANES) between 1999 and 2012. The association of HCV infection status (including HCV infection, current HCV infection, and past HCV infection) with hypertension, systolic blood pressure (SBP), and diastolic blood pressure (DBP) were explored using logistic or linear regression analyses respectively. Results A total of 25,850 participants (age≥18 years) were enrolled in the current study, including 14,162 participants with hypertension. After adjusting for all covariates, HCV infection/current HCV infection was not associated with hypertension and SBP compared to participants with non-HCV infection (OR: 1.34,95% CI 0.96–1.87/1.31 95% CI 0.91,1.91, β: -0.92, 95% CI -2.7–0.86/-0.35 95% CI -2.51,1.81, respectively). HCV infection/current HCV infection was only associated with elevated DBP (β: 4.1,95% CI 2.57–5.63/4.24,95% CI 2.27–6.21). However, there was no correlation with past HCV infection in participants with hypertension, SBP, and DBP compared to those with non-HCV infection (OR: 1.23,95% CI 0.59–2.54; β: -3.79, 95% CI -7.67–0.08 and 2.28 95% CI -0.36–4.92, respectively). Conclusion In a representative sample of US adults, it was found that both HCV infection and current HCV infection were independently linked to higher DBP. However, there was no association between past HCV infection and DBP.